2012
DOI: 10.2196/jmir.2238
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Electronic Patient Portals on Patient Care: A Systematic Review of Controlled Trials

Abstract: BackgroundModern information technology is changing and provides new challenges to health care. The emergence of the Internet and the electronic health record (EHR) has brought new opportunities for patients to play a more active role in his/her care. Although in many countries patients have the right to access their clinical information, access to clinical records electronically is not common. Patient portals consist of provider-tethered applications that allow patients to electronically access health informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
323
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 344 publications
(330 citation statements)
references
References 26 publications
4
323
0
3
Order By: Relevance
“…After removing duplicates and initial screening of titles and abstracts, 42 papers were retrieved for detailed evaluation. [24,25,26] which were part of another main study [6,27,28], leading to a total of 20 unique reviews [3,6,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. The overall process of review selection was …”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After removing duplicates and initial screening of titles and abstracts, 42 papers were retrieved for detailed evaluation. [24,25,26] which were part of another main study [6,27,28], leading to a total of 20 unique reviews [3,6,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. The overall process of review selection was …”
Section: Search Resultsmentioning
confidence: 99%
“…There were three reviews reporting positive effects of patient portals on better adherence to treatment and medication regimen [6,28,38]. However, overall evidence of improvement in quality of care was limited [6], and there was a lack of studies investigating long-term health outcomes [32]. As most of the patient portal evaluations targeted online interventions for chronic disease management (e.g.…”
Section: Narrative Synthesis Of the Evidence Of Benefitsmentioning
confidence: 99%
“…These new technologies have increased patient empowerment, decreased office visit rates and phone calls to physicians, and improved adherence to treatment. 14,15 However, little is known about the use of web-based patient portals among the transplant recipient patient population. Studies have indicated that due to the high prescription burden, transplant recipients are interested in web-based applications to assist in their complex medication management.…”
Section: Introductionmentioning
confidence: 99%
“…[6,8] It has been suggested that various telehealth technologies can assist in reducing both burden and cost of CVD around the world. [1,[9][10][11] Various technologies such as remote patient monitoring systems, mobile phone intervention programs, electronic health databases, smartphone apps, instant messaging, video calling and patient portals are just a few of the innovative technology concepts repeatedly used to increase adherence to treatment, disease prevention, and health management programs. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] In addition, health technologies have also been shown to increase adherence to various treatment and motivation for selfmanagement of chronic diseases.…”
Section: Introductionmentioning
confidence: 99%